The role of protective rules in determining the applicable law in consumer protection - PhD. professor: Nizam Jabbar tialb; Assistant professor Osama Mohsen Jassim (The college of law and political science journal, 2024)
Is the result of the legislative development that has recently appeared on many contractual formulas that did not exist in practice, and in all areas of life, especially in the field of tourism, so the time sharing system appeared, which allows the beneficiaries to benefit and spend holidays and vacations in tourist resorts or religious places, which requires research and study of this contractual system and its compatibility with the legal provisions stable in the general rules, whether in the theory of the contract or in the named contracts. And highlight the role of protective rules in protecting the consumer beneficiary, choosing the appropriate law and closest to his interest, and excluding other laws that harm his interest if they are imposed on him by the owner of the company or the usufruct right.